Effects on the Cell Barrier Function of L-Met and DL-HMTBA Is Related to Metabolic Characteristics and m6A Modification - Zuo, Fangrui; Wei, Hongkui; Peng, Jian; Li, Shengqing; Zhou, Yuanfei (Frontiers in Nutrition, 2022)
Methionine is a substrate for protein synthesis and participates in many other biological events via its metabolism. We have previously demonstrated significant differences in the metabolism of L-methionine (L-Met) and its precursor DL-2-hydroxy-4-methylthiobutyric acid (DL-HMTBA) in IPEC-J2 cells. When DL–HMTBA is added to the diet, intracellular methionine (Met) sources also contain the natural form of L-Met. Then, what is the effect on Met metabolism when these two Met sources exist simultaneously? Moreover, the effects of metabolic differences on cell function remain unclear. In this study, it was found that when the proportion of L-Met to DL–HMTBA was ≤ 40%:60%, Met transmethylation was promoted and when the proportion of L-Met to DL-HMTBA was ≤ 85%:15%, Met trans-sulfuration and regeneration were improved. In addition, DL-HMTBA improved the cell barrier function when the ratio of L-Met to DL-HMTBA was ≤ 40%:60%. This finding may be due to the decrease in the proportion of S-adenosylmethionine to S-adenosylhomocysteine and mRNA N6-methyladenosine (m6A) levels, which increase the mRNA stability and protein expression of tight junction zona occludens-1. To sum up, the effects of L-Met and DL–HMTBA on Met metabolism, especially transmethylation, suggest that DL–HMTBA has the potential to influence the intestinal barrier function of animals through epigenetic processes.